LEGAL PROTECTION OF WORKERS WITH DISABILITIES IN FULFILLING WORK SAFETY AND HEALTH RIGHTS - Luh Kurnia Dharma Pertiwi, Ni; Bagiastra, I Nyoman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The purpose of this paper is to analyze forms of legal protection for workers with disabilities in fulfilling their rights to occupational safety and health and to determine the obstacles in fulfilling their rights to occupational safety and health for workers with disabilities. The research method used for normative research is a robust approach that focuses on the study of the application of norms or rules in positive law. The data sources used in this normative legal research are secondary data in the form of primary legal materials, namely laws, and secondary legal materials in the form of legal books. The type of approach used in this writing is a statutory approach. The results of this writing show that. The protection of occupational safety and health is regulated in Article 86 paragraph (1) of the Manpower Law. A form of legal protection for workers with disabilities in fulfilling their rights to occupational safety and health can be in the form of fulfilling their rights to accessibility as regulated in the Law on Persons with Disabilities.There are obstacles in fulfilling these rights; employers or companies have not been able to fulfill the rights that workers with disabilities should receive. Therefore, it is crucial for the Government to conduct regular supervision to monitor the implementation of the provisions in fulfilling the rights to occupational safety and health for workers with disabilities.